Review of self-healing effect on shape memory alloy (SMA) structures - Hassan, Mohd Roshdi; Mehrpouya, Mehrshad; Emamian, Sattar; Sheikholeslam, Mohammad Nassir (Trans Tech Publications, 2013)
Self-healing has usually an emphasis on special materials that is metallic materials. When there is a minor damage, almost all biological organisms, even complex ones, have the ability to repair themselves. Recently, a novel field of materials science is constituted by self-healing in organic materials or material systems and it is rapidly expanding. These materials have a particular ability to heal themselves. The initial crack is healed to the point that upon reloading, a new crack is formed next to the original, rather than the original crack reopening. Only simple heating can reverse transformation and cause reinforcement for these cracks. The shape memory alloy wires are activated by heating the system and therefore the healing begins. Due to the heat, the wires relapse to their original shape at the shape change in martensite to austenite transition temperature. The concentration of most of the studies so far has been on polymers and ceramics and the reason is that it includes self-healing in non-metallic materials. Also, they are more convenient than including it in metallic materials. In this review paper the design principles of self-healing materials and their improvement methods are investigated.